Inventarisasi Tumbuhan Famili Rosaceae di Sekitar Kebun Biologi UIN Sunan Gunung Djati Bandung - Muhammad Fahmi Nur Arif; Muhammad Fahmi Alamsyah; Ateng Supriatna (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
This study aims to inventory the Rosaceae family of plants around the UIN Sunan Guning Djati Bandung biological garden. The Rosaceae vary depending on the cultivar, being thorny shrubs with woody stems that reach high. One of the Rosaceae family, namely roses which are spread throughout the world. This study uses qualitative methods with direct observation and documentation to facilitate the research process. Data were analyzed by means of literature studies in the form of scientific journals, reference books and the internet. The research sample is Rosa hybrida or rose plants around the garden. The results showed that there was one species of rosa hybrida in the biology garden of UIN Sunan Gunung Djati Bandung.